Occurrence of bartonella genotypes in bats and associated streblidae flies from Maranhão State, Northeastern Brazil - Braga, Maria Do Socorro Costa Oliveira; Gonçalves, Luiz Ricardo [UNESP]; da Silva, Thiago Merighi Vieira [UNESP]; Costa, Francisco Borges; Pereira, José Gomes; Dos Santos, Larissa Sarmento; Neta, Alcina Vieira de Carvalho; de Arruda, Roberto Carlos Negreiros; Mesquita, Eric Takashi Kamakura de Carvalho; Chaves, Daniel Prazeres; Melo, Ferdinan Almeida; Lopes, Jady Lima; et al. (FapUNIFESP (SciELO), 2020)
Bartonella is a genus of emerging zoonotic bacteria that are mainly associated with mammalian erythrocytes and endothelial cells. Bats are natural reservoirs for a variety of important pathogens that impact human and animal health. Recent reports have highlighted the role of bats and bat flies in the maintenance of Bartonella. Here, we showed that none of the 29 bat DNA blood samples obtained from five bat species in São Luís Island, state of Maranhão, northeastern Brazil, were positive for Bartonella in qPCR assays targeting nuoG. On the other hand, three out of 15 DNA samples (20%) from flies in the family Streblidae were positive for Bartonella. The BLASTn results showed that the gltA and rpoB sequences shared identities ranging from 97.2% to 100%, with Bartonella sequences amplified from bats or bat flies from Costa Rica and Brazil. These findings were supported by phylogenetic analyses based on Bayesian inferences. The present study showed that Bartonella genotypes are present in bat flies, thus shedding some light on the distribution of bat fly-related Bartonella genotypes in South America.
Ocorrência de genótipos de bartonella em morcegos e moscas streblidae no estado do Maranhão, Nordeste do Brasil
Keywords: Bartonellosis; Chiroptera; Hippoboscoidea; PCR